(3GdfbV GdNajs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe GdYdi GdCYdi MGce GdMcGe ef dGjONd ai GdNhGWQ hGdChgGe MQha HSe Gddg GdQMef GdQMje s
(3BNQgG (B:s
(3hgj Chd Sfjf XghQ YHO ehdGfG heedhcg gGOi GdeSJLjHjf GdefJbe ef GdeTQcjf HSja ehdGfG Ld PcQg dGTQjc dg hdG eYHhO ShGg hMSHfG ehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds